Limotettix carniolicus sp. nov., a new West-Palaearctic leafhopper species (Hemiptera, Cicadomorpha, Cicadellidae) - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2017)
A new species of the leafhopper genus Limotettix Sahlberg 1871 is described. In outer appearance it is similar to L. ochrifrons, L. aviger and related species. It is easily distinguishable from all other species of the genus by the peculiar shape of aedeagus and by its smaller body size. The species was found in western Slovenia in a montane intermediate bog living on Eleocharis quinqueflora, most probably monophagously. It is univoltine and hibernates in the egg stage. Adults have been found from early July until mid-August. Temporary, the species is considered as highly vulnerable and in danger of extinction.
Keywords: barja; Cicadellidae; Cicadomorpha; Hemiptera; intermediate bog; leafhoppers; Limotettix carniolicus; new species; nove vrste; Slovenia; Slovenija; škržatki; zoology